Adipokines: diagnostic and prognostic markers for oral diseases - Chaudhry, Saman Zafar; Sarah Ghafoor, (Journal of the Pakistan Medical Association, 2023)
Adipose tissue or fat tissue is a loose connective tissue that consists mainly of adipocytes. Adipocytes are classified on the basis of their secretory origin, differentiation, distribution, cell characteristics, such as amount of mitochondria, size and type of lipid droplets, and expression of uncoupled protein-1. Adipocytes secrete adipokines that are divided as white adipokines, brown adipokines and beige adipokines. Adipokines have been used as diagnostic and prognostic markers for different oral diseases. Irisin, chemerin, resistin, adiponectin, zinc alpha 2 macroglobulin, leptin, visfatin, tumour necrosis factor-alpha and interleukin-6 are some important adipokines associated with oral diseases, such as dental caries, periodontal diseases, recurrent aphthous stomatitis, oral cancers, oral premalignant lesions, Sjogren’s syndrome, Kawasaki disease and Behcet’s disease. The current narrative review was planned to focus on the pathophysiological role of adipokines in oral diseases and their role as biomarkers for early diagnosis and prompt treatment.